Genocide and resistance Nr. 55(1) - Šutinienė, Irena; Gelžinis, Arvydas; Vyšniauskas, Arūnas; Burinskaitė, Kristina; Matimaitytė, Rūta; Ilmjärv, Magnus; Ludvigsen, David Sætre; Chomej, Dawid (Genocidas ir rezistencija, 2024)
Full Issue